2020
DOI: 10.1186/s13075-020-02200-4
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-18 and fibroblast growth factor 2 in combination is a useful diagnostic biomarker to distinguish adult-onset Still’s disease from sepsis

Abstract: Objective: To identify potential biomarkers to distinguish adult-onset Still's disease (AOSD) from sepsis. Method: We recruited 70 patients diagnosed with AOSD according to the Yamaguchi criteria, 22 patients with sepsis, and 118 age-matched controls. Serum levels of 40 cytokines were analyzed using multi-suspension cytokine array. We performed a cluster analysis of each cytokine in the AOSD and sepsis groups in order to identify specific molecular networks. Further, multivariate classification (random forest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 35 publications
1
14
1
Order By: Relevance
“…Besides, IL-18 showed the highest discriminating ability between AOSD and COVID-19 in the ROC analysis of the putative markers. These findings suggest that exaggerated production of IL-18 is highly characteristic of active AOSD, resonating with previous reports showing IL-18 as a diagnostic marker and indicator of disease activity in AOSD (16,48,49). Blocking IL-18 with recombinant IL18 BP (tadekinig alfa) has therapeutic efficacy for AOSD (22) but has yet to be applied to COVID-19 treatment now.…”
Section: Discussionsupporting
confidence: 84%
“…Besides, IL-18 showed the highest discriminating ability between AOSD and COVID-19 in the ROC analysis of the putative markers. These findings suggest that exaggerated production of IL-18 is highly characteristic of active AOSD, resonating with previous reports showing IL-18 as a diagnostic marker and indicator of disease activity in AOSD (16,48,49). Blocking IL-18 with recombinant IL18 BP (tadekinig alfa) has therapeutic efficacy for AOSD (22) but has yet to be applied to COVID-19 treatment now.…”
Section: Discussionsupporting
confidence: 84%
“…To assess the diagnostic ability of IL-18 in AOSD, it is necessary to conduct comparative studies with control diseases that have pathologies and clinical findings similar to those of AOSD. Between 2001, when Kawashima et al were the first to report that serum IL-18 was markedly elevated in patients with AOSD, and the present investigation's writing, several studies have compared serum IL-18 levels in AOSD and other inflammatory diseases in adults (8,10,12,(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32). The most common control group in those reports was rheumatic diseases, mainly such as rheumatoid arthritis, SLE, and Sjogren's syndrome.…”
Section: Discussionmentioning
confidence: 75%
“…those studies. The control disease in the remaining studies was infection, especially sepsis in two studies (30,31), which is categorized as 'hyperferritinemic syndrome,' similar to MAS or Still's disease (33). These studies also showed that the serum IL-18 levels in patients with sepsis were approximately 100 pg/mL, which is significantly lower than the levels in AOSD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Serum IL-18 levels have been shown to be significantly higher in patients with AOSD than in other inflammatory diseases, and its concentration correlates with disease activity. IL-18 may therefore be a useful therapeutic target for AOSD as well as a biomarker for differential diagnosis between AOSD and sepsis (35)(36)(37)(38)(39). Until now, there were no other biomarkers with high sensitivity and specificity.…”
Section: Discussionmentioning
confidence: 99%
“…Grouping AOSD disease activity status by our method was somewhat arbitrary and divergent, so it may cause the results to be biased with other research units. Last, previous studies had proposed that PCT, IL-18 combined with fibroblast growth factor 2 (FGF 2) and modified Pouchot Score including elevated serum ferritin levels ( 12 , 33 , 36 ) could be a useful diagnostic tool to distinguish AOSD and sepsis. However, as our study was a retrospective design, many laboratory values such as ferritin, PCT, serum cytokine levels such as IL-18, IL-6 and interferon were not performed in all patients at that time.…”
Section: Discussionmentioning
confidence: 99%